2016
DOI: 10.1186/s12961-016-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Global health equity in United Kingdom university research: a landscape of current policies and practices

Abstract: BackgroundUniversities are significant contributors to research and technologies in health; however, the health needs of the world’s poor are historically neglected in research. Medical discoveries are frequently licensed exclusively to one producer, allowing a monopoly and inequitable pricing. Similarly, research is often published in ways that make it inaccessible. Universities can adopt policies and practices to overcome neglect and ensure equitable access to research and its products.MethodsFor 25 United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This approach has been recommended by the World Health Organization's Consultative Expert Working Group and has demonstrated successes in Canada and the United States [9,34]. A study examining equitable licensing practices in the United Kingdom has found a similarly low rate of equitable licensing adoption [5]. Equitable licensing is nearly nonexistent at German medical faculties.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been recommended by the World Health Organization's Consultative Expert Working Group and has demonstrated successes in Canada and the United States [9,34]. A study examining equitable licensing practices in the United Kingdom has found a similarly low rate of equitable licensing adoption [5]. Equitable licensing is nearly nonexistent at German medical faculties.…”
Section: Plos Onementioning
confidence: 99%
“…Recent studies assessing global health research at universities in the United States of America (USA), Canada, and the United Kingdom (UK) identified significant shortcomings in the equitable dissemination of research results [3][4][5]. In terms of the share of health research funding compared to corresponding global burden of disease, research on poverty-related and neglected diseases is underfinanced by a factor of five at universities in the UK [5]. Similar imbalance in the allocation of resources for neglected diseases research were found for North American research universities [6].…”
Section: Introductionmentioning
confidence: 99%
“…By engaging in inequitable technology transfer practices, such as the exclusive licensing of a novel health technology to a private company or a spin-off, universities enable the downstream formation of pricing monopolies that limit affordable access to health technologies. 1 2 The WHO defines health technologies as ‘the application of organized knowledge and skills in the form of devices, medicines, vaccines, procedures and systems developed to solve a health problem and improve quality of lives’. 3 Worldwide nearly 2 billion people lack access to essential medicines and 100 million people are pushed into extreme poverty annually due to their inability to pay for their healthcare expenditures.…”
Section: Inequitable Technology Transfer Practices As Structural Violencementioning
confidence: 99%
“…2 14 The dissemination of university research should be rooted in the concept of global health equity, which envisions a needs-based approach to health and well-being of humanity rather than one based on economic and social privileges. 1 To uphold these commitments to inclusive knowledge dissemination in the interest of the public, universities should ensure during the technology transfer process that the global community receives a return on investing into R&D. 1 6 15 Indeed, pharmaceutical companies often claim that the exclusivity of patents and pricing monopolies promote risk taking in early innovation, yet universities are often the source of important publicly funded research that underlies novel health technologies. 6 Universities therefore have the opportunity to prevent the creation of pricing monopolies and access barriers downstream, and a responsibility towards the global public who contributed to R&D funding to do so.…”
Section: Equitable Technology Transfer As a Means To Challenge Inequities In The Biomedical Innovation Systemmentioning
confidence: 99%
“…They described an 18-month process to develop a consultative research agenda and questions for health systems research in which a wide range of stakeholders participated and which produced a useful starting point. Gotham et al [31] examined the landscape of current policies and practices in relation to global health equity in United Kingdom universities’ research, and suggested various improvements.…”
Section: Editorialmentioning
confidence: 99%